Building cover crop expertise with citizen science in the upper Midwest: supporting farmer innovation in a time of change - Ingram, Mrill (Frontiers in Sustainable Food Systems, 2023)
Abstract: The use of cover cropping, as one element in a continuous living cover approach, has the potential to protect water quality and promote soil health, but overall U.S. acreage in cover crops as well as adoption rates remain low. Research on behavioral barriers to cover crop use indicates a lack of information about locally suitable practices and cover crop varieties, as well as the additional management complexity of cover cropping and a high degree of uncertainty in outcomes, especially in areas with shorter growing seasons. This paper shares results from a citizen science project on cover cropping in Wisconsin. The goals of the project include i) generating more geographically distributed data on cover crop performance in the state; and ii) better understanding of farmer decision-making around growing practices, barriers, and motivations for cover cropping. While citizen science, as it relies on physically distributed members of the public in data generation, is well established as an avenue for generating environmental data, the approach is less explored as a tool for understanding the contexts of individual behavior and identifying potential leverage points for change, including on-farm innovation and experimentation. In this paper I review a case study of a collaborative cover crop research and outreach effort in Wisconsin that included a modified citizen science element. I share project findings regarding cover crop results, farmer decision-making about cover cropping in Wisconsin, as well as insights into how the citizen science model can be used to expand our understanding of decision-making contexts, and responsive outreach efforts.